Re-envisioning the delta: Alternative futures for the heart of California - William Eisenstein; Matt Kondolf; John Cain (University of California, Institute of Urban and Regional Development (IURD), 2007)
Re-Envisioning the Delta is an initiative of the Department of Landscape Architecture and Environmental Planning of the University of California, Berkeley. Our aim is to conduct research on land-use change in the Delta, its environmental, infrastructural, social, and economic consequences, and to work with agencies and stakeholders to develop alternative futures for this critically important region. Towards this end, we have conducted research documenting for the first time the actual extent of urbanization potential in the Delta (drawing upon general plans from all jurisdictions in the region, development documents and analysis of sequential aerial photographs), held a workshop with key Delta leaders in February 2006 to better define the issues, hosted a public symposium in March 2006 on the Berkeley campus, held a student design competition for a Delta park, facilitated a design charrette in the Delta in October 2006 for stakeholders to develop alternative future visions for the region, and are currently undertaking a cumulative effects analysis for urbanization in the Delta and a further charrette.
Keywords: 330